Interaction of Purinergic P2X4 and P2X7 Receptor Subunits - Schneider, Markus; Prudic, Kirsten; Pippel, Anja; Klapperstück, Manuela; Braam, Ursula; Müller, Christa E.; Schmalzing, Günther; Markwardt, Fritz (Frontiers in Pharmacology, 2017)
P2X4 and P2X7 are members of the P2X receptor family, comprising seven isoforms (P2X1–P2X7) that form homo- and heterotrimeric non-specific cation channels gated by extracellular ATP. P2X4 and P2X7 are widely coexpressed, particularly in secretory epithelial cells and immune and inflammatory cells, and regulate inflammation and nociception. Although functional heteromerization has been established for P2X2 and P2X3 subunits expressed in sensory neurons, there are contradictory reports regarding a functional interaction between P2X4 and P2X7 subunits. To resolve this issue, we coexpressed P2X4 and P2X7 receptor subunits labeled with green (EGFP) and red (TagRFP) fluorescent proteins in Xenopus laevis oocytes and investigated a putative physical interaction between the fusion proteins by Förster resonance energy transfer (FRET). Coexpression of P2X4 and P2X7 subunits with EGFP and TagRFP located in the extracellular receptor domains led to significant FRET signals. Significant FRET signals were also measured between C-terminally fluorophore-labeled full-length P2X41-384 and C-terminally truncated fluorescent P2X71-408 subunits. We furthermore used the two-electrode voltage clamp technique to investigate whether human P2X4 and P2X7 receptors (hP2X4, hP2X7) functionally interact at the level of ATP-induced whole-cell currents. Concentration–response curves and effects of ivermectin (P2X4-potentiating drug) or BzATP (P2X7-specific agonist) were consistent with a model in which coexpressed hP2X4 and hP2X7 do not interact. Similarly, the effect of adding specific inhibitors of P2X4 (PSB-15417) or P2X7 (oATP, A438079) could be explained by a model in which only homomers exist, and that these are blocked by the respective antagonist. In conclusion, we show that P2X4 and P2X7 subunits can form heterotrimeric P2X4/P2X7 receptors. However, unlike observations for P2X2 and P2X3, coexpression of P2X4 and P2X7 subunits does not result in a novel electrophysiologically discriminable P2X receptor phenotype.